Oncoplastic Surgery: Does Patient and Medical Specialty Influences the Evaluation of Cosmetic Results? - de Oliveira-Junior, Idam [UNESP]; Brandini da Silva, Fabíola Cristina; Nazima, Flávio; Ribeiro, José Carlos; Castellani, Laurinda; Zucca-Matthes, Gustavo; Maciel, Maria do Socorro; Biller, Gabriele; José da Silva, Jonathas; Sarri, Almir José; Aloísio da Costa Vieira, René [UNESP] (Elsevier, 2020)
Background: Oncoplastic surgery (OS) has added plastic surgery concepts and techniques to the breast cancer surgery. However, reports of the impact of OS on cosmesis after breast-conserving surgery (BCS) are limited in the literature. Patients and Methods: This cross-sectional prospective study included patients who underwent BCS. The patients self-evaluated the cosmetic outcome of the breasts and had them photographed. The photos were evaluated by BCCT.core software and by 6 breast surgeons (mastologists and plastic surgeons) using the Harvard, Garbay, and Fitoussi scales. Kappa and weighted kappa tests were used to analyze agreement for categorical variables; for continuous variables, the interclass correlation index and the chi-square test to analyze the association between the OS and the symmetrization. Results: A total of 300 patients were evaluated: 228 (76.0%) underwent traditional BCS and 72 (24.0%) underwent OS, and of these, 37 (51.4%) underwent contralateral symmetrization surgery. In the evaluation of the cosmetic result, the correlation between patients and observers (BCCT.core and surgeons) was weak; between the 2 groups of surgeons, the correlation was moderate (Fitoussi scale) and excellent (Garbay scale). Plastic surgeons are more critical for evaluating cosmetic results; they considered it good or excellent in 30.0% whereas patients, mastologists, and BCCT.core results considered it so in 78.8%, 34.0%, and 30.0%, respectively. In terms of cosmesis, OS and symmetrization did not influence the results in this study with long follow-up. Conclusion: Patients’ self-evaluation reported better cosmesis than surgeons’ analyses. Plastic surgeons were the most critical. OS and symmetrization did not influence the results.

Oncoplastic surgery (OS) has established itself as a safe treatment for breast cancer; however, its cosmetic evaluation remains little explored. After evaluating 300 patients undergoing breast-conserving treatment, with or without OS, we found that patients are more satisfied with the cosmetic outcome compared to observers (software and surgeons), and OS did not affect these results.
Keywords: Breast cancer; Conserving surgery; Conserving treatment; Cosmetic techniques; Oncoplastic